2009
DOI: 10.1103/physreve.79.016204
|View full text |Cite
|
Sign up to set email alerts
|

Poincaré recurrences and transient chaos in systems with leaks

Abstract: In order to simulate observational and experimental situations, we consider a leak in the phase space of a chaotic dynamical system. We obtain an expression for the escape rate of the survival probability applying the theory of transient chaos. This expression improves previous estimates based on the properties of the closed system and explains dependencies on the position and size of the leak and on the initial ensemble. With a subtle choice of the initial ensemble, we obtain an equivalence to the classical p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
102
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(116 citation statements)
references
References 79 publications
9
102
1
4
Order By: Relevance
“…This universal output directionality of single modes was proven without ambiguity in experiments on a liquid-jet microcavity (Lee et al, 2007c). Using this concept provided numerical evidence that all long-lived modes in the limaçon cavity (23) In the case of mixed phase space the chaotic saddle is divided into hyperbolic and nonhyperbolic components (Altmann, 2009). The mechanism of escape of electromagnetic radiation along the unstable manifold works also in this case as demonstrated by experiments on microwave cavities of quadrupolar shape .…”
Section: Chaotic Saddle and Its Unstable Manifoldmentioning
confidence: 90%
See 2 more Smart Citations
“…This universal output directionality of single modes was proven without ambiguity in experiments on a liquid-jet microcavity (Lee et al, 2007c). Using this concept provided numerical evidence that all long-lived modes in the limaçon cavity (23) In the case of mixed phase space the chaotic saddle is divided into hyperbolic and nonhyperbolic components (Altmann, 2009). The mechanism of escape of electromagnetic radiation along the unstable manifold works also in this case as demonstrated by experiments on microwave cavities of quadrupolar shape .…”
Section: Chaotic Saddle and Its Unstable Manifoldmentioning
confidence: 90%
“…A systematic and clear discussion of this extended version of the chaotic saddle and its relation to the ergodic theory of transient chaos can be found in (Altmann, 2009;Altmann et al, 2013). Altmann (2009) pointed out that the unstable manifolds of short periodic orbits (which are part of the chaotic saddle) close to the critical line as discussed by Schwefel et al (2004) are parallel to the unstable manifold of the chaotic saddle and therefore lead to nearly the same far-field emission.…”
Section: Chaotic Saddle and Its Unstable Manifoldmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27] From the mathematical point of view, a billiard is defined by a connected region Q & R D , with boundary @Q & R DÀ1 which separates Q from its complement. Basically, they are settled in three classes, namely (i) integrable, (ii) ergodic, and (iii) mixed.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the RTS is capable of describing the relevant aspects of the dynamics in complex systems. In this context, we mention that the RTS is able to describe universal algebraic decays in Hamiltonian systems [2][3][4], including random walk penetration of the Kolmogorov-Arnold-Moser (KAM) islands [5,6], biased random walk to escape from KAM island [7], DNA sequence [8], synchronization of oscillator [9], generalized bifurcation diagram of conservative systems [10], fine structure of resonance islands [11], transient chaos in systems with leaks [12], among others.…”
Section: Introductionmentioning
confidence: 99%